2021
DOI: 10.3390/cells10020360
|View full text |Cite
|
Sign up to set email alerts
|

Social Defeat Stress during Early Adolescence Confers Resilience against a Single Episode of Prolonged Stress in Adult Rats

Abstract: Early-life adverse experiences (first hit) lead to coping strategies that may confer resilience or vulnerability to later experienced stressful events (second hit) and the subsequent development of stress-related psychopathologies. Here, we investigated whether exposure to two stressors at different stages in life has long-term effects on emotional and cognitive capabilities, and whether the interaction between the two stressors influences stress resilience. Male rats were subjected to social defeat stress (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…However, our RSD model did not induce anxiety-like behavior, altered locomotion, or social dysfunction, as the time spent in the center of the open field, the distance travelled, and the social interaction were not affected. Previous studies using the RSD protocol during juvenile age or adulthood have shown contradictory results, as either an increase in anxiety and social dysfunction ( MacKay et al, 2017 ; Mancha-Gutiérrez et al, 2021 ; Mancini et al, 2021 ), or no effect ( Moraga-Amaro et al, 2022 ; Mouri et al, 2018 ) have been reported. Many factors may explain such differences, including housing conditions, differences in the RSD procedure, its duration and timing, and the interval between the RSD and the behavioral tests.…”
Section: Discussionmentioning
confidence: 94%
“…However, our RSD model did not induce anxiety-like behavior, altered locomotion, or social dysfunction, as the time spent in the center of the open field, the distance travelled, and the social interaction were not affected. Previous studies using the RSD protocol during juvenile age or adulthood have shown contradictory results, as either an increase in anxiety and social dysfunction ( MacKay et al, 2017 ; Mancha-Gutiérrez et al, 2021 ; Mancini et al, 2021 ), or no effect ( Moraga-Amaro et al, 2022 ; Mouri et al, 2018 ) have been reported. Many factors may explain such differences, including housing conditions, differences in the RSD procedure, its duration and timing, and the interval between the RSD and the behavioral tests.…”
Section: Discussionmentioning
confidence: 94%
“…For example, repeated social defeat in social mammals triggers activation of subconscious parts of the brain, which in turn promotes nervousness (Rajalingam et al, 2021;Wohleb et al, 2014). In rats, exposure to social stress may be seen as momentary submissive supine posture, freeze or flight, and later vulnerability toward cued fear memory dysfunction (Mancini et al, 2021). In humans, the changes may be manifested as ''negative affect'', i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Sex specific effect is also reported for Wistar rats, when acute stress during adolescence increases anxiety behavior in male Sprague-Dawley rats, while females are not affected ( Lovelock and Deak, 2019 ). Most studies report increased anxiety-like behaviors in adult male rodents after a single or repeated mild stress during the same developmental period ( Tsoory et al, 2007 ; Mancini et al, 2021 ; Meyer et al, 2021 ). In contrast, a 3-day stress in the same EA period increases anxiety-like measures in the OFT and the EPM in both adult male and female rats ( Jacobson-Pick and Richter-Levin, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Would females genetically predisposed to increased passive coping be more resilient to the effects of adolescent stress than males of the same strain? Would the resilience generated in females after the double hit of adolescent stress and the stress of FST in adulthood be like the resilience generated by social defeat in adolescence to the single stress in adulthood ( Mancini et al, 2021 )? Future studies modifying the nature of the stressor in adolescence and the strain of animals used could in part answer this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation